2000
DOI: 10.1148/radiology.215.1.r00ap38147
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Portal Venous Stenosis in Children and Adolescents with Segmental Hepatic Transplants: Long-term Results

Abstract: Percutaneous treatment of portal venous stenoses is effective and long lasting in children with reduced-size hepatic transplants. In patients with elastic or recurrent lesions, portal venous stents have excellent long-term primary patency despite continued patient growth. Successful, percutaneous transhepatic venoplasty eliminates the need for surgical revision, portacaval shunting, or repeat transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
198
2
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(208 citation statements)
references
References 12 publications
2
198
2
6
Order By: Relevance
“…In order to prevent post-interventional bleeding from the puncture tract 1) it is recommended to puncture the intrahepatic portal vein system as peripherally as possible (in this way the risk of arterial bleeding is minimized), and 2) embolization of the puncture tract has been performed, e. g. by cylinders of collagen, coils, N-butyl cyanoacrylate, Gelfoam and Gelfoam cubes [1 -5, 7]. In several studies there were no postinterventional bleeding complications [1, 3, 11], even when the puncture tract was not embolized [11]. However, in other studies bleeding complications were reported: 1) Cheng et al…”
mentioning
confidence: 99%
“…In order to prevent post-interventional bleeding from the puncture tract 1) it is recommended to puncture the intrahepatic portal vein system as peripherally as possible (in this way the risk of arterial bleeding is minimized), and 2) embolization of the puncture tract has been performed, e. g. by cylinders of collagen, coils, N-butyl cyanoacrylate, Gelfoam and Gelfoam cubes [1 -5, 7]. In several studies there were no postinterventional bleeding complications [1, 3, 11], even when the puncture tract was not embolized [11]. However, in other studies bleeding complications were reported: 1) Cheng et al…”
mentioning
confidence: 99%
“…10 For a residual significant stenosis or a recurrent stenosis within a few months after balloon angioplasty, the metallic stent placement should be considered. 11,12 However, there is a retransplantation case report about graft failure caused by portal thrombus after the placement of a portal vein stent for portal stenosis. 13 Measuring the long-term outcomes of larger patient pools is necessary for evaluation of portal vein stent for portal stenosis after liver transplantation.…”
Section: 5mentioning
confidence: 99%
“…The placement of metallic stents also has been reported for treatment of recurrent or nonresponsive elastic stenosis (Funaki et al, 2000;Zajko et al, 1994). In the largest patient series for which data are available, a very good patency rate of 100% was found at 46 months after treatment with angioplasty and metallic stent placement (Funaki et al, 2000). A transhepatic puncture of the portal vein is performed with a 21-gauge needle while using US for guidance.…”
Section: Portal Vein Stenosismentioning
confidence: 99%
“…14). The persistence of a pressure gradient of more than 5 mm Hg has been considered an indication for metallic stent placement (Funaki et al, 2000). Coil or gelfoam embolization of transhepatic needle tracts can be done to reduce the risk of bleeding.…”
Section: Portal Vein Stenosismentioning
confidence: 99%